2002
DOI: 10.1080/00420980220142709
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Local Retail Property Markets on the Basis of Rental Growth Rates

Abstract: Diversification strategies for the property element of portfolios have traditionally been undertaken on a sectoral/regional basis, primarily due to data restrictions. However, the standard regions in the UK are defined for administrative purposes and are likely, therefore, to be composed of heterogeneous property markets. The development of an alternative classification, based on local property markets, is investigated. This is based on annual retail rental growth rates and is developed using cluster analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…This methodology has been widely used not only in the context of business cycles (for example Altavilla 2004, Harding & Pagan 2001, 2002, but also in office markets (Jackson et al 2008). However, both concordance measures can be difficult to assess and interpret.…”
mentioning
confidence: 99%
“…This methodology has been widely used not only in the context of business cycles (for example Altavilla 2004, Harding & Pagan 2001, 2002, but also in office markets (Jackson et al 2008). However, both concordance measures can be difficult to assess and interpret.…”
mentioning
confidence: 99%
“…The metrics used are Ward's method of clustering and the squared Euclidian distance measure, seeking to maximise both within-cluster homogeneity in area characteristics and between-cluster heterogeneity. These metrics replicate those used to cluster local property markets, proxied by Local Authority (LA) areas, in studies by Jackson (2002) and Jackson and White (2005a, b) and, in part, Hamelink et al (2000) who use Ward's method as the amalgamation rule. The method of analysis begins with 432 separate clusters (each comprising one LA area) and ends with one cluster containing all 432 areas.…”
Section: The Uk Office Of National Statistics (Ons) Area Classificationmentioning
confidence: 99%
“…In terms of the total UK direct property market, it was estimated at the end of 2003 (the date of the empirical data utilised in this study) that the capital value of the commercial property market was £611 billion, with 80 percent (£489 billion) in the largest retail, office and industrial sectors (Key and Law, 2005 Hamelink et al, 2000;Jackson, 2002;and Lee and Byrne, 1998, in the UK, the latter also using local economic fundamentals) and local economic characteristics. In the US similar studies are found in Hartzell et al, 1986Hartzell et al, , 1987Malizia and Simons, 1991;Mueller and Ziering, 1992;Mueller, 1993;Goetzmann and Wachter, 1995;and Ziering and Hess, 1995.…”
Section: Asset Classes and Market Fundamentals Asset Classesmentioning
confidence: 99%
“…Specifically, the studies of Hamelink, Hoesli, Lizieri, and MacGrgeor (2000) and Jackson (2002) are revisited. The first examines 157 local property markets, across the office, retail and industrial sectors and concludes that 'conventional UK administrative and statistical regional classifications do not provide useful information in structuring a portfolio strategy' (Hamelink et al, 2000, p. 341) but that outperformance is possible using clusters more reflective of market drivers, even with fewer classes.…”
Section: Introductionmentioning
confidence: 99%